Development and characterization of voriconazole-oxalic acid dihydrate cocrystals for enhanced pharmaceutical performance - Nijhawan, Monika; Jidige, Bhavana; Aleti, Rajeswari; Gunnam, Sailaja; Saxena, Trapti (Prospects in Pharmaceutical Sciences, 2025)
Pharmaceutical cocrystallization is a promising alternative for improving the solubility and dissolution rate or manipulating other physical properties of active pharmaceutical ingredients. The objective of this investigation was to study the effect of cocrystallization to improve physicochemical properties of voriconazole (VZ). Liquid assisted grinding method was attempted for preparation of cocrystals. Melting point, Fourier transformation infrared spectroscopy (FTIR), powder X-ray diffraction (PXRD), and differential scanning calorimetry (DSC) techniques were employed to investigate the hydrogen bonding interaction, crystallinity and thermal behaviour of prepared cocrystals respectively. The pharmaceutical cocrystals were successfully obtained with oxalic acid dihydrate (OAD) in 2:1 stoichiometric ratio. The physicochemical properties of VZ and corresponding cocrystals were assessed in terms of saturation solubility and dissolution performance. The VZ cocrystals showed enhanced solubility and dissolution rate as compared with VZ. The VZ cocrystals (4.179 mg/mL) showed higher solubility in 0.1 N hydrochloric acid than VZ (3.140 mg/mL). Cocrystals showed higher dissolution rate than VZ. The enhancement in dissolution rate of VZ cocrystal from OA was 2.28-fold within 10 min.